Sustainable Development Goals through Productive Fisheries Waqf - Putri Rizka Citaningati; Kamaluddin Kamaluddin (Institut Agama Islam Negeri Kendari, 2022)
Waqf is one of the financial instruments in Islamic economics besides Zakat. Currently, the management of waqf funds has intensified by the Government and Islamic financial institutions because of its enormous potential in Indonesia. One of them is the Productive Seafood Waqf program implemented by Global Waqf-ACT. However, studies on productive waqf, especially those that discuss the agricultural sector in improving the fishers' economy, are still minimal. Therefore, this qualitative explanatory research aims to formulate a productive seafood waqf scheme implemented by Global Waqf-ACT that could help the achievement of the Sustainable Development Goals (SDGs). The result shows that productive seafood waqf could provide more benefits, especially for the anglers in the agricultural sector. Another benefit that can be achieved is the productive seafood waqf managed by Global Waqf-ACT also supports several main points in the SDGs, such as no poverty and hunger, providing good health, life below water, and partnership for the goals.